GREEN E-SPORTS BUILDING DESIGN WITH FUTURISTIC PRINCIPLE APPROACH - Alif Sirajuddin Bahri; Samsul Bahri (Jurnal Arsitektur ARCADE, 2024)
Advances in technology have made some activities shift from offline to online. This condition also occurs in sports activities, namely electronic sports (e-sports). The public's enthusiasm for welcoming e-sports is accompanied by the emergence of e-sports teams that have training facilities for players. However, in its implementation, most e-sports training facilities are wasteful in electrical energy consumption. Based on this phenomenon, the author offers the design of an environmentally friendly e-sports training facility by applying a green building nuanced design through an approach to futuristic architectural principles. This research uses architectural design methods to produce an e-sports training facility design with green building nuances. The design of the building site is placed in the middle of the land, to provide undeveloped areas on all sides of the site for green areas to reduce global warming. The faÃ§ade of the building uses wide glass combined with a curtain wall frame so that natural lighting in the space in the building is more optimal. The placement of line ornaments on the outer side, as secondary skin, reduces the radiance of sunlight in the afternoon. The use of prefabricated materials has advantages in terms of shape, size, and ease of installation. The use of ACP combined with exposed steel frames without repainting is a measure to reduce pollution and a representation of honesty.